Questioning the Climate Crisis: A Contrastive Analysis of Parascientific Discourses - Curry, Niall (Nordic Journal of English Studies, 2024)
Research on climate crisis discourses occupies an important niche in applied linguistics. While it is known that cross-linguistic and cross-cultural variation can play key roles in differentiating the construction of climate knowledge, there remains a dearth in multilingual work on climate-themed parascientific discourses. Addressing this gap, this paper presents a corpus-based contrastive analysis of direct questions in parascientific texts in English, French, and Spanish. The results demonstrate that direct questions are a core feature of climate-themed academic news blogs in each language and that they are significantly more frequent in French than in English. Second, they indicate key thematic domains in which experts ask questions in each language, including science and technology in English, science in French, and politics and society in Spanish. Third, they offer insight into the metadiscursive and discursive roles of direct questions in an emerging, multilingual parascientific genre. These roles include helping authors to manage texts, make arguments, and frame hypothetical situations. Thematically, questions address climate science, social and political issues, and impact and adaptation in English, French, and Spanish, climate scepticism in English and French, and climate communication in Spanish.